Cultural diplomacy frames in BRICS: formation of foundations, challenges and prospects - Delovarova, L.F.; Turarbekova, D.B. (Farabi Journal of Social Sciences, 2024)
The article examines the BRICS countries' cultural diplomacy in the light of globalization and its impact on international relations. Nowadays, when international issues and dangers necessitate coordinated actions to maintain peace and stability, cultural diplomacy becomes a crucial instrument to foster understanding and collaboration between nations. This article explores the successes and difficulties of cultural diplomacy among the BRICS nations, as well as its importance in promoting multipolarity and balancing international relations. The 16th BRICS Summit Kazan Declaration, which was approved at the summit and assigns the job of updating cultural diplomacy strategies in light of shifting geopolitical circumstances, receives particular attention. The authors investigate how cultural diplomacy and its external strategy in the BRICS nations and worldwide trends may be impacted by recent political and social developments. The study draws conclusions regarding the importance of cultural diplomacy as a means of strengthening the system of international relations, challenges and prospects. Keywords: BRICS, cultural diplomacy, multilateralism, 16th BRICS summit.